The allocation of German aid: Self-interest and government ideology - Axel Dreher; Peter Nunnenkamp; Maya Schmaljohann (Kiel Institute for the World Economy (IfW), 2013)
We investigate the importance of geo-strategic and commercial motives for the allocation of German aid to 138 countries over the 1973-2010 period. We find that geo-strategic and - less robustly - commercial motives matter. When we relate geo-strategic and commercial motives to the political color of the German government in general, and the Ministry for Economic Cooperation and Development and the Federal Foreign Office in particular, we find their importance to increase under socialist leadership. Socialist leadership also decreases the amount of aid commitments, controlled for other factors.
Keywords: F35; F53; F63; 330; aid allocation; government ideology